Desenvolvimento de sabonete líquido antifúngico para uso ginecológico a partir de extrato das folhas de Myracrodruon urundeuva Allemão (aroeira-do-sertão) - Rodrigues, João Felipe Pinheiro (2025)
Gynecological health is an important element for female well-being, and vulvovaginal candidiasis (VVC) is one of the most common reasons women seek health care. In this context, the aroeira-do-sertão (Myracrodruon urundeuva Allemão) is a botanical species rich in phenolic compounds and with notable medicinal properties that make it a promising candidate for gynecological applications. Given the use of natural products in the treatment and prophylaxis of gynecological conditions, this study was carried out with the aim of developing a liquid soap for intimate use with antifungal action from aroeira-do-sertão fluid extract (EFA). The leaves of the adult plant species were collected, dried and crushed, and the quality of the plant drug was characterized. To obtain the EFA, maceration followed by percolation with a 60% hydroalcoholic solution was used, and its microbiological, physical and chemical quality control was performed, including phytochemical identification and quantification of its active markers, polyphenols and total tannins. Furthermore, the antifungal action of the EFA against standard strains of Candida was evaluated by means of the agar diffusion technique to determine the minimum lethal concentration (MLC). The EFA was used as an active pharmaceutical ingredient (API) in the pharmacotechnical development of aroeira-do-sertão liquid soap (SAS), which had its quality and antifungal action evaluated by the same methods described for the plant derivative, being compared to the results of a commercial liquid intimate soap containing aqueous extract of aroeira-da-praia (Schinus terebinthifolius – SAP). The extractive conditions to which the plant drug was subjected resulted in obtaining EFA with adequate microbiological, physical and chemical quality, with a total polyphenol content equal to 189.08 (±0.0306) mg EAG/g of EFA, of which only 17.83 (±0.02) mg EAG/g of EFA - 9.43% - correspond to total tannins. The assay to evaluate the antifungal activity of EFA demonstrated its action against C. albicans ATCC 10231, C. krusei ATCC 6258, C. parapsilosis ATCC 22019 and C. tropicalis ATCC 13803, with CLM of 0.5% w/v. The SAS with 2.5% w/v of EFA presented quality compatible with use as a liquid soap for gynecological use and an antifungal effect similar to that observed for the IFA of plant origin. EFA and SAS exhibited greater antifungal activity than SAP, possibly due to the latter's qualitative and quantitative composition, especially regarding the concentration of aqueous extract of aroeira- da-praia and its bioactives, which were not reported by the manufacturer, despite having other quality characteristics comparable to SAS. The present study allowed the development of a liquid soap for gynecological use with proven antifungal action against yeasts of the genus Candida from a characterized extract of aroeira-do-sertão leaves, with the aim of using it in intimate hygiene and prophylaxis of VVC through initiatives such as the Farmácias Vivas Program.